165k views
2 votes
Someone help me please ASAP

Someone help me please ASAP-example-1
User Mlepage
by
5.2k points

1 Answer

2 votes


((8)/(27))^{(-2)/(3)}

=
((27)/(8))^{(2)/(3)

=
\sqrt[3]{((27)/(8))^(2)}

=
\sqrt[3]{((27*27)/(8*8))}

=
(3*3)/(2*2)

=
(9)/(4)

Error: Student did not use the negative sign properly

*********************************************************************


(x^(-6)y^(6))(x^{(-1)/(6)}y^(5))

=
x^(-6)*x^{(-1)/(6)}*y^(6)*y^(5)

=
x^{-6-{(1)/(6)}}*y^(6+5)

=
x^{{(-37)/(6)}}y^(11)

=
\frac{y^(11)}{x^{(37)/(6)}}

Error: Student multiplied the exponents instead of adding them

**********************************************************************


(\frac{2m^{(1)/(4)}}{n^(4)})^(-4)

=
(2^(-4)m^(-1))/(n^(-16))

=
\frac{n^(16)}{{2^(4)m^(1)}}

=
\frac{n^(16)}{{16m}}

Error: Student did not distribute the exponent properly AND did not use the negative sign properly

User Tom Castle
by
5.5k points